Literature Review on the Appropriateness of Medication Prescription in Chronic Kidney Disease Patients: Focus on Antibiotic Use - Ariesa Oktamauri; Nadia Farhanah Syafhan; Santi Purna Sari (Green Publisher Indonesia, 2025)
Chronic Kidney Disease (CKD) significantly impacts pharmacokinetics and pharmacodynamics, altering drug metabolism and excretion, thus increasing the risk of drug toxicity. CKD patients are more susceptible to infections, which contribute to significant morbidity and mortality. This underscores the importance of appropriate antimicrobials used in this population. This literature review explores recent findings on medication prescribing practices, dose adjustments, and factors affecting appropriateness, especially in antibiotic use for CKD patients. A comprehensive literature search was conducted using six databases to identify studies published from 2015 to 2024. Twenty-six studies were included. This literature review found that prevalence of inappropriate prescriptions in CKD patients ranges widely between 10% to 77.1% and from 30% to 34,9% specifically for antibiotic, with higher rates observed in outpatient settings compared to hospital environments. Antibiotics, antidiabetic agents, antihypertensive, nutraceuticals, and electrolytes are frequently inappropriately prescribed. Factors influencing inappropriate prescription include comorbidity, severity level of kidney disorder, age, and polypharmacy. The antibiotics most commonly prescribed inappropriately include cefazolin, meropenem, oral sulfamethoxazole-trimethoprim, nebulised colistin, vancomycin, and piperacillin-tazobactam. This study emphasizes the mixed and limited evidence regarding the clinical outcomes of antibiotics dose adjustments in CKD patients. While some studies suggest that antibiotics dose adjustments improve therapeutic outcomes and reduce adverse events, others show no significant impact. Further research is needed to understand the impact of this intervention, as these outcomes may be influenced by various factors. Enhanced education and collaboration between healthcare providers are critical to improving the accuracy of antibiotic prescriptions and ensuring patient safety in CKD management.